Generalised Impedance Converters with only Transconductance Elements and Grounded Capacitors - Iqbal A. Khan; Muslim T. Ahmed; Nigar Minhaj (Active and Passive Electronic Components)
Novel generalised impedance converters are presented, which use only transconductance elements and/or grounded capacitors for the realisation of a wide variety of immittance functions. The generalised impedance converters can be used in the realisation of low sensitivity continuous time filters. The use of transconductance elements and grounded capacitors in the realisation of continuous time filters lend to electronic tunability and compatibility to integration in contemporary IC technologies. The generalised impedance converters are also verified using PSPICE-based simulation.